Children in the Digital Age: Health, Behavioral, Learning Impacts, and Management Strategies - Rishikesh Upadhyay (Nusantara Journal of Behavioral and Social Science, 2026)
The growing reliance on digital technology among children and adolescents is becoming a noticeable global trend. While these technologies offer valuable opportunities to enhance learning and modernize educational practices, they also disrupt traditional methods and reshape how young people interact, think, and develop. Digital tools are not only embedded in everyday life-they are actively transforming social relationships, personal identities, and even our understanding of what it means to be human in a digitally connected world. As these technologies continue to influence behavior, health, and education, it is crucial to examine both their potential benefits and unintended consequences. This article explores how deeply digital technologies are impacting children’s development, highlighting the complex and evolving role they play in shaping the future of society. The findings have important practical implications for parents, schools, teachers, and policymakers, emphasizing the need to promote balanced digital engagement, strengthen digital literacy, and develop evidence-informed policies that support children's healthy development and well-being.